Exploring magnetic XY behavior in a quasi-2D anisotropic triangular lattice of Cu(II) by functionalized graphene - Gupta, Kriti; Dadwal, Arun; Jha, Plawan Kumar; Jain, Anil; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Inorganic Chemistry, 2020)
Study on magnetism in two-dimensional (2D) spin-lattices is advancing rapidly. In this work, phase-pure botallackite (Bo) (Cu-2(OH)(3)Br), a quasi-2D S = 1/2 anisotropic triangular spin-lattice is stabilized over 2D reduced graphene oxide (rGO) nanosheets via simple oxidation-reduction reaction chemistry. In comparison to polycrystalline Bo, such an anchoring resulted in the oriented growth of Bo crystallites in the Bo-rGO system. The Bo-rGO nanocomposite was found to be magnetically active with a Neel transition at 8.9 K, crossing over to possible XY anisotropy at similar to 5 K-as revealed by complementary dc and ac susceptibility measurements-an unprecedented observation in the field assigned to an interfacial effect. This work demonstrates the potential usage of nonmagnetic 2D functionalized graphene to significantly modulate the magnetic properties of 2D spin-lattices.